An examination of the challenges and awareness presented by the transfer of born-digital records in the public sector: A case study of Türkiye - CENGİZ, EMİNE (My University, 2023)
In the Turkish public sector, official policy, and practice on the transfer of digital records to the Turkish State Archives has yet to be implemented, and the consequences of this have yet to be fully identified or comprehended. As such there is a need for research and recommendations on this problem. The purpose of this study is to provide a situational analysis of the transfer process of born-digital records to the national archives in Türkiye, by identifying the challenges faced in the digital transfer process, with the aim of raising awareness among public bodies. The survey method was used to collect data about the digital transfer process in Türkiye. A total of 120 public bodies participated in the survey. The originality value of this study can be said to be significant as of the target population, 120 Turkish public sector bodies were surveyed to determine their challenges and level of awareness regarding the born-digital transfer process. In addition to the high number of Turkish public bodies surveyed, this is the first study of its kind in Türkiye on digital transfer and its processes. The findings of the research revealed that public bodies in Türkiye are not currently ready for digital transfer. The findings also highlighted that the legal and technical infrastructure required for digital transfer in the public sector was inadequate. The research findings also concluded that staff working in the public sector require training in the processes related to the transfer of digital records. In line with the research data recommendations have been made regarding the digital transfer process in Türkiye.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)